Fast Food Consumption Behavior of Culinary Science Students at Padang State University - Melpita, Monica Rivany; Faridah, Anni; Yuliana, Yuliana; Holinesti, Rahmi (Universitas Negeri Padang, 2025)
Fast food consumption among students is quite high, although they have knowledge about choosing good food, not all students apply it in their food consumption. This study aims to describe the level of knowledge, attitudes and actions of IKK Culinary Arts students at Padang State University in consuming fast food. This type of research is quantitative descriptive research. The population of this study were active students of IKK Culinary Arts UNP class of 2019-2023 who had taken nutrition courses totaling 481 people. The sampling technique used the Proportionate Stratified Random Sampling technique totaling 218 people. The data collection technique was carried out by distributing questionnaires (questionnaires) via google form which had been tested for validity and reliability. Furthermore, the data was analyzed through descriptive analysis with the assessment categorization method based on the frequency of the assessment percentage and the analysis requirements test using SPSS version 25.00. The results showed that the level of student knowledge about fast food was in the good category with a percentage of 59%, the attitude towards consuming fast food was in the moderate category with a percentage of 44%, and the actions of students in consuming fast food were in the moderate category with a percentage of 40%. From these results it can be interpreted that fast food consumption in IKK Tata Gaga UNP students is still within safe limits.